STUDENTS' MENTAL MODEL IN POLARIZED EYEGLASSES - Husna, Hanna Nurul (Jurnal Pengajaran MIPA, 2020)
The aim of this study was to investigated students’ mental model on light concept and its application in polarize glasses. 42 students of Optometry Program were used in this study, which categorized into two grups: newbie group and advance group. The data was collected through paper and pencil test using three open ended questions and descriptively analyzed. The study showed that almost all the students have understanding about light concept and image forming in the eyes, and beam rays model was most used in their depiction. Understanding about polarize concept showed better for advance group than newbie group, and most of students from both group used beam rays model too. Understanding about principle of polarized glasses showed better for newbie group than advance group. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana gambaran mental model mahasiswa pada konsep cahaya dan aplikasinya pada kacamata polarize. Penelitian ini melibatkan 42 mahasiswa program studi Refraksi Optisi dengan pembagian kelompok pemula dan kelompok mahir. Data dikumpulkan melalui paper and pencil test dengan menggunakan tiga pertanyaan terbuka dan dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa hampir semua mahasiswa memahami mengenai konsep cahaya dan pembentukan bayangan di mata dengan dominasi penggambaran cahaya menggunakan model beam rays. Pemahaman terhadap konsep polarisasi lebih ditunjukkan di kelompok pemula daripada kelompok mahir dan sebagian besar dari kedua kelompok tersebut menggambarkan dengan menggunakan beam rays model. Pemahaman terhadap prinsip kerja kacamata polarize lebih ditunjukkan kelompok mahir dibandingkan kelompok pemula. Kata kunci: mental model, polarized eyeglasses   Keywords: mental model, eyeglasses, polarized